Easy Access to Novel Tetrahydro-1-benzazepine-2-carboxylic Acids and Tetrahydro-1-benzazepines Carrying [a]-Fused Heterocyclic Units from 2-(Allylaryl)glycinates - Guerrero, Sergio Andrés; Ramírez, Juan E.; Sanabria, Carlos M.; Acosta, Lina M.; Cobo, Justo; Nogueras, Manuel; Palma, Alirio (Synthesis, 2020)
A concise, efficient, and versatile approach to access novel tetrahydro-1H-benzo[b]azepine-2-carboxylic acids and tricyclic tetrahydro-1-benzazepines carrying [a]-fused heterocyclic units is reported. The easily accessible 2-(allylaryl)glycinates were used as starting material to synthesize, via the corresponding 1,4-epoxycycloadducts, the required key intermediate benzo[b]azepine-2-carboxylates. Hydrolysis of the latter afforded the targeted benzo[b]azepine-2-carboxylic acids. The key intermediate was also converted into N-2-chloroacetyl derivatives which, in turn, were transformed into the corresponding tricyclic target hexahydrobenzo[f]pyrazino[1,2-a]azepine-1,4-diones by reaction with benzylamine or aminoethanol. The reaction of the common intermediate with hydrazine gave the corresponding intermediate carbohydrazides, which, by reaction with trimethoxymethane, were transformed into another tricyclic target tetrahydrobenzo[f][1,2,4]triazino[4,5-a]azepin-4(3H)-ones. Full spectroscopic characterization (IR, HRMS, and 1H and 13C NMR) is also reported for each compound.
Keywords: 2-(allylaryl)glycinates; intramolecular 1,3-dipolar cycloaddition; reductive cleavage; cyclocondensation; tricyclic fused-[a]-1-benzazepines